Pengaruh Pemanfaatan Teknologi Informasi, Kejelasan Sasaran Anggaran, dan Pengawasan terhadap Akuntabilitas Pengelolaan Dana Desa: Studi Empiris pada Pemerintah Desa di Kabupaten Buleleng Bagian Barat - Ni Kadek Sumarni Dewi; Nyoman Ayu Wulan Trisna Dewi; Made Aristia Prayudi (Universitas Pendidikan Ganesha, 2026)
This study aims to examine the effect of information technology utilization, budget goal clarity, and supervision on the accountability of village fund management. This research employs a quantitative approach using primary data collected through Likert-scale questionnaires. The population and sample consist of village officials, including village heads, village secretaries, and financial officers in village governments in the western part of Buleleng Regency, covering Banjar, Seririt, Gerokgak, and Busungbiu districts. Data were analyzed using multiple linear regression with the assistance of IBM SPSS 26. The results indicate that information technology utilization, budget goal clarity, and supervision each have a positive effect on the accountability of village fund management. This implies that the more optimal the use of information technology, the clearer the budget goals, and the more effective the supervision, the higher the accountability of village fund management.